Social capital and economic growth: empirical evidence from OIC countries - Hantoro Ksaid Notolegowo; Samsubar Saleh (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2019)
Abstract. This research investigates the effect of constructive social capital such as religious tolerance, political participation, and marriage; and destructive social capital such as the corruption culture and discrimination behavior towards the economic growth rate of member countries of the Islamic Cooperation Organization (OIC) 2014-2017. The results of the research estimation using the technique of fixed effect (FE) from the panel data of the OIC countries show that religious tolerance measured using the freedom of religion index (FRI) shows a positive and significant effect on the economic growth rate; political participation as measured by political rights index (PRI) has a significant negative effect on the economic growth rate; marriage measured using the percentage of married woman (PMW) has a positive effect on the economic growth rate but is not significant; corruption culture measured using corruption perception index (CPI) has a negative and not significant effect on the economic growth rate; and discrimination behavior measured using discrimination and violence against minorities index (DVI) shows a negative and not significant effect on the economic growth rate.Keywords: Social Capital, Constructive, Destructive, Economic Growth, OIC Abstrak. Penelitian ini menginvestigasi pengaruh modal sosial konstruktif (constructive social capital) seperti toleransi beragama, partisipasi politik, dan pernikahan, serta modal sosial destruktif (destructive social capital) seperti budaya korupsi dan perilaku diskriminasi terhadap tingkat pertumbuhan ekonomi negara-negara anggota Organisasi Kerjasama Islam (OKI) 2014-2017. Hasil estimasi penelitian menggunakan teknik analisis fixed effect (FE) dari data panel negara-negara OKI menunjukkan bahwa toleransi beragama yang diukur menggunakan freedom of religion index (FRI) menunjukkan pengaruh positif dan signifikan terhadap tingkat pertumbuhan ekonomi; partisipasi politik yang diukur menggunakan political rights index (PRI) memberikan pengaruh negatif signifikan terhadap tingkat pertumbuhan ekonomi; pernikahan yang diukur menggunakan percentage of married woman (PMW) memiliki pengaruh positif terhadap tingkat pertumbuhan ekonomi namun tidak signifikan; budaya korupsi yang diukur menggunakan corruption perception index (CPI) memberikan pengaruh negatif dan tidak signifikan terhadap tingkat perumbuhan ekonomi; dan perilaku diskriminasi yang diukur menggunakan discrimination and violence against minorities index (DVI) menunjukkan pengaruh negatif dan tidak signifikan terhadap tingkat pertumbuhan ekonomi.Kata kunci: Modal Sosial, Konstruktif, Destruktif, Pertumbuhan Ekonomi, OKI